Modelling of Transition to Adulthood for Adolescents at Social Risk - Baranauskienė, Ingrida; Krauzienė, Milda; Virbalienė, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The transition from the education system to the adult labor market system is mediated by interacting subjective and structural factors specific to each country including its educational system structure and organization, social and cultural context, demographic factors, labor market and role of state in shaping labor supply and demand. The article reviews the theoretical analysis of transition to adulthood of adolescents at social risk attending day care center. Adolescents at social risk attending day care center have not enough social skills. According to the study, social risk adolescents attending day care center lack of self-awareness skills at most. Essay analysis revealed that these teens are unable to organize their nutrition properly, purchase foods themselves and rationally manage their money. After applying the social skills program the most obvious change in social risk teenagers attending day care center was better self-knowledge skills. These adolescents gained knowledge of healthy nutrition. They would consider before buying certain goods is it necessary. In their essay about personal finance savings social risk adolescents in day care center expressed a more rational approach to money.